Examining Southeast Asia’s diplomacy on nuclear disarmament and nuclear security: shared norms and a regional agenda - Caballero-Anthony, Mely (2022)
Member-states of the Association of Southeast Asian Nations (ASEAN) support the norms of nuclear disarmament and nuclear security through diplomatic efforts at the global level and regional efforts to promote nuclear safety and security. T his is demonstrated in how ASEAN helped push for negotiation of the Treaty on the Prohibition of Nuclear Weapons (TPNW) and its eventual passage, as well as ongoing efforts to promote regional cooperation in advancing nuclear security and nuclear safety. Regional frameworks and mechanisms like the ASEAN Network of Regulatory Bodies on Atomic Energy (ASEANTOM), the ASEAN Regional Forum, and the East Asia Summit provide the platforms for ASEAN to advance its diplomacy in promoting the norms of nuclear governance.